Pain response of resistance training of the paravertebral musculature under radiotherapy in patients with spinal bone metastases – a randomized trial - Rief, Harald (BioMed Central, 2014)
BACKGROUND: To compare pain response outcomes for patients with spinal bone metastases treated with resistance training of the spinal musculature versus passive physical therapy during radiotherapy (RT). METHODS: In this randomized trial, 60 consecutive patients were treated from September 2011 until March 2013 within one of the two groups: resistance training (Arm A) or passive physical therapy (Arm B) with thirty patients in each group during RT. The course of pain according to visual analog scale (VAS), concurrent medication, and oral morphine equivalent dose (OMED) were assessed at baseline, three months, and six months after RT. Pain response was determined using International Bone Consensus response definitions. RESULTS: The course of VAS in the intervention group (Arm A) was significantly lower both during and after RT (AUC, p < .001). The use of analgetic medication showed the same result, with significantly fewer analgetics being necessary both during and after RT in arm A (p < .001). In the course of time, the OMED decreased in arm A, but increased in arm B. After 6 month, 72.2% of patients in arm A, and 22.2% in arm B were responders (p = .014). CONCLUSION: Our trial demonstrated that guided isometric resistance training of the paravertebral muscles can improve pain relief over a 6-months period in patients with stable spinal metastases. Importantly, the intervention was able to reduce OMED as well as concomitant pain medication. The trial is registered in Clinical trial identifier NCT 01409720 (http://www.clinicaltrials.gov/) since 2(nd) of August 2011.